PERAN LEMBAGA KOMISI YUDISIAL MEMBAWA PERUBAHAN SISTEM PERADILAN DI INDONESIA - rahmat, muhfadly; Rahmat, Muh. Fadly (Animha Law Journal, 2025)
This article aims to analyze the role of the Judicial Commission (Komisi Yudisial, KY) in shaping social change and strengthening the Indonesian justice system. The study applies a literature review approach to explore the dynamics of KY’s authority, its impact on public trust, and its contribution to legal reform. The findings indicate that KY promotes judicial integrity through ethics supervision, enhances transparency in the judiciary, and empowers public participation. However, challenges remain, including limited authority, institutional resistance, and lack of public awareness. Strengthening KY’s authority and fostering broader collaboration are essential for building a fair and accountable justice system.